Circulating proprotein convertase subtilisin-kexin type 9, all-cause mortality, and cardiovascular mortality: the Ludwigshafen Risk and Cardiovascular Health study - Silbernagel, Günther; Kleber, Marcus E.; März, Winfried (European journal of preventive cardiology, 2017)
Background: It is unclear whether proprotein convertase subtilisin-kexin type 9 (PCSK9) concentrations may be useful for cardiovascular risk stratification. Design: The LUdwigshafen RIsk and Cardiovascular health (LURIC) study is a prospective observational registry of patients who were referred for coronary angiography. Methods: Circulating PCSK9 was measured in 2139 participants of the LURIC study. There was a follow-up for all-cause and cardiovascular mortality with a median (interquartile range) duration of 10.1 (8.1-10.8) years. Results: The mean (standard deviation) age of the participants (1470 males and 669 females) was 62.6 (10.8) years, body mass index 27.3 (4.0) kg/m2, and low density lipoprotein cholesterol 114 (33) mg/dl. The mean (standard deviation) PCSK9 concentration was 220 (82) ng/ml. Of the participants, 1035 (48.4%) were on statins. Use of statins was associated with significantly lower low density lipoprotein cholesterol (106 vs 121 mg/dl, p < 0.001) but significantly higher circulating PCSK9 (244 vs 197 ng/ml, p < 0.001). A total of 674 (31.5%) study participants died from any cause and 431 (20.1%) from cardiovascular diseases. In the entire cohort, the third vs first tertile of PCSK9 was not associated with the risk of death from any cause (hazard ratio = 1.09, p = 0.367) and from cardiovascular diseases (hazard ratio = 1.09, p = 0.476). In participants without statins, the third vs first PCSK9 tertile was modestly associated with increased all cause mortality (hazard ratio = 1.34, p = 0.029) but not with cardiovascular mortality (hazard ratio = 1.25, p = 0.194). Conclusions: Circulating PCSK9 may be upregulated by statin use and does not appear to be useful for cardiovascular risk stratification.